Hair Graying: Mechanisms, Prevention, and Innovative Treatment Strategies - literature review - Monika Kienanh Do; Karolina Kazimierska; Dominika Zaliwska; Adrianna Kraszkiewicz; Natalia Paduszyńska; Marta Justyna Gonciarz; Dominika Karolina Adamiec; Anna Dąbrowska; Monika Anna Kamińska; Magdalena Czach (Nicolaus Copernicus University in Toruń, 2024)
Hair graying, or canities, is a complex biological process characterized by the progressive loss of hair pigment, often leading to aesthetic and psychological concerns. This review delves into the multifactorial nature of hair graying, examining the underlying biochemical and physiological mechanisms. Key contributors include oxidative stress, genetic and environmental factors, and disturbances in melanogenesis and signaling pathways such as Notch and Kit. Our extensive literature review from PubMed, involving 33 scientifically rigorous papers, explores the efficiency of various strategies aimed at delaying or preventing hair graying. We highlight the roles of antioxidants, lifestyle modifications, and advanced therapeutic approaches like genetic therapy and liposome delivery systems. Additionally, we explore the impact of diet and UV protection, among other factors, on maintaining hair pigmentation. This review underscores the intricate interplay of biochemical processes in hair graying and sheds light on promising interventions for managing this natural yet often unwelcome sign of aging.